The moment as a factor in emotional well-being - King, James Roy (Journal of religion and health, 1986)
The moment is a phenomenon of increasing interest to observers of human experience, whether their concern be literature, art, theology, psychology, history, or sports. For in the moment an individual's sense of reality is heightened and his capacity for choice is intensified. Among the situations where our sense of reality can both reflect and produce a significant level of emotional well-being are moments where presentness is keenly felt, interpersonal relationships, kinetic experiences in sports, the sense of being inspired, moments of commitment, highly dramatic presentations of the self, and peak experiences. The literature is extensive.